2020
DOI: 10.7759/cureus.7259
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment Hematological Variations and the Role of Hemoglobin as a Predictor of Disease-free Survival in Stage 2 Breast Cancer Patients

Abstract: The primary objective of this study was to determine post-treatment variations in the hematological profile of stage 2 breast cancer patients and investigate the influence of disease stage and treatment pattern on these changes. The secondary objective was to evaluate the role of post-treatment hemoglobin as a predictor of disease-free survival. MethodsThis prospective, observational study included 177 stage 2, female, breast cancer patients. Treatment included surgery, chemotherapy, radiotherapy, and hormonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(25 reference statements)
2
5
0
Order By: Relevance
“…The study also found poor treatment outcomes in patients with persistently low levels of Hb (Lee et al, 2017). The observation that red blood cell (RBC) concentration was significantly lower among the patients agrees with a previous study that found significantly lower RBC levels in breast cancer patients (Raza et al, 2020). Considering the role of inflammation in breast cancer pathology (Colotta et al, 2009), inflammatory blood markers such as white blood cell count could have prognostic potential in breast cancer patients (Park et al, 2019).…”
Section: Study Of Sialic Acids Level In Breast Cancersupporting
confidence: 89%
See 1 more Smart Citation
“…The study also found poor treatment outcomes in patients with persistently low levels of Hb (Lee et al, 2017). The observation that red blood cell (RBC) concentration was significantly lower among the patients agrees with a previous study that found significantly lower RBC levels in breast cancer patients (Raza et al, 2020). Considering the role of inflammation in breast cancer pathology (Colotta et al, 2009), inflammatory blood markers such as white blood cell count could have prognostic potential in breast cancer patients (Park et al, 2019).…”
Section: Study Of Sialic Acids Level In Breast Cancersupporting
confidence: 89%
“…Consequently, the development of models that utilize inflammatory blood parameters to predict treatment outcomes among breast cancer patients has been suggested (Zhu et al, 2021). Lower levels of Hb and RBC observed in breast cancer patients necessitate that treatment options consider possible anaemia in breast cancer patients, as some treatments could exacerbate anaemia (Raza et al, 2020). Ibrahim et a.l., 2022…”
Section: Study Of Sialic Acids Level In Breast Cancermentioning
confidence: 99%
“… 20 , 35 RBC is an important nutrition-related prognostic factor for cancers and decreased RBC has been found to associate with poor survival in breast cancer and colorectal cancer. 36 , 37 In the present study, we also revealed that a reduced preoperative RBC level was an independent prognostic factor in TSCC.…”
Section: Discussionsupporting
confidence: 78%
“…Hematological abnormalities can be observed both before and after cancer treatment. Pretreatment hematological abnormalities are mostly due to suppression of hematopoiesis via bone marrow infiltration [ 8 , 9 ]. Several studies confirm that pretreatment anemia, neutropenia, and thrombocytopenia were found to be common in breast cancer patients [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%